Repressed Inflation And Interest Rates - Kafka, Folke (1979)
Currently there is confusion about the role of interest rates, due in part to the inflationary process is given and it is relatively new to a country with little tradition of inflation. It says, for example, that the interest rate should not increase because of business failures would cause or that the interest rate should increase because it needs to encourage savings. This article aims to provide the framework for discussion relevant to analyze the economic policies that have been taken and to be taken in the future with respect to the interest rate.